Development of Soils Derived from Weathered Sedimentary, Granitic and Ultrabasic Rocks in South Kalimantan Province: I. Mineralogical Composition and Chemical Properties - MARKUS ANDA; NATA SUHARTA; SOFYAN RINTUNG (Jurnal Tanah dan Iklim (Indonesian Soil and Climate Journal), 2000)
Limited information is available on chemical propertiesand mineralogical composition of soils in South Kalimantan Province. The objective of this study is to assess the develop derived from weathered sedimentary, granitic and ultrabasic rocks with respect to soil management. Field investigations and laboratory analyses were performed to compare morphological properties, particle sizes, mineralogical compositions of sand and clay fractions, organic C, N, pH, extractable acidity, P retention, exchangeable cations, cation exchange capacity, and oxides of iron and aluminium. The results. show the AY-14 pedon has a higher degree of development followed by MA-86 and SW-89, respectively as indicated by mineralogical composition and chemical properties. Although the three pedons are dominated by kaolinite, the AY- 14 pedon (developed from an ultrabasic rock) has no weatherable minerals and vermiculite but has high opaques, low quartz and colloid surfaces bearing positive charge. On the other hand, weatherable minerals are only found in SW-89. The MA-86 and SW-89 (developed from granitic and sedimentary rocks, respectively) have low opaques, high quartz, a minor proportion of vermiculite, and colloid surfaces bearing negative charges. These findings suggest that the AY-14 has a higher degree of development than MA-86 and SW-89. Comparison between MA-86 and SW-89 indicated that the former has lower clay cation exchange capacity (CEC) and contains no weatherable minerals indicating that the MA-86 has a higher degree of development than the SW-89. The values of exchangeable cations, CEC of soil and clay, and ECEC were low in all three pedons. The magnitude of each value was lower in the AY-14 followed by MA-86 and SW-89, respectively. In contrast, P retention and iron oxides were the highest in the AY- 14 pedon followed by MA-86 and SW-89, respectively. The three pedons have very acid to acid pH, and low C and N contents. Based on chemical properties and mineralogical composition, the three pedons need different management practices. The soil derived from ultrabasic rock (AY-14) needs higher phosphate fertilizer due to its high P retention, higher organic matter and lime than soils derived from granitic rock (MA-86) and sedimentary rock (SW-89) in order to increase CEC, nutrient availability and soil pH.